2021
DOI: 10.3390/molecules26113171
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Serotonin in Breast Cancer Stem Cells

Abstract: Breast tumors were the first tumors of epithelial origin shown to follow the cancer stem cell model. The model proposes that cancer stem cells are uniquely endowed with tumorigenic capacity and that their aberrant differentiation yields non-tumorigenic progeny, which constitute the bulk of the tumor cell population. Breast cancer stem cells resist therapies and seed metastases; thus, they account for breast cancer recurrence. Hence, targeting these cells is essential to achieve durable breast cancer remissions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…Kim et al reported that patients who received tramadol after breast cancer surgery had a decreased risk of postoperative recurrence and mortality, with the anti-tumor effect of tramadol appearing to involve inhibition of proliferation, induction of apoptosis, and effects on the serotonin 2B receptor and transient receptor potential vanilloid-1 expression [ 63 ]. More generally, antagonists of serotonin biosynthesis, transport, and activity appear to diminish breast cancer stem cell viability [ 64 ]. Serotonin production in a tumor sample may be a predictor of poor prognosis [ 65 ].…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al reported that patients who received tramadol after breast cancer surgery had a decreased risk of postoperative recurrence and mortality, with the anti-tumor effect of tramadol appearing to involve inhibition of proliferation, induction of apoptosis, and effects on the serotonin 2B receptor and transient receptor potential vanilloid-1 expression [ 63 ]. More generally, antagonists of serotonin biosynthesis, transport, and activity appear to diminish breast cancer stem cell viability [ 64 ]. Serotonin production in a tumor sample may be a predictor of poor prognosis [ 65 ].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, some molecular markers, such as CD44 + /CD24 -/low ( Al-Hajj et al, 2003 ; Sheridan et al, 2006 ), ALDH1 + ( Ginestier et al, 2007 ; Morimoto et al, 2009 ), CD133 ( Kim et al, 2015 ), CD61 ( Vaillant et al, 2008 ), CD49f ( Ye et al, 2017 ), and CXCR4 ( Ablett et al, 2014 ; Trautmann et al, 2014 ), can be used as biomarkers to identify BCSCs, and may serve as therapeutic targets for small molecular inhibitors. Therefore, many researchers realize that targeting BCSCs is crucial to achieve long-lasting remission of breast cancer ( Gwynne et al, 2021 ). In experimental research, the common and unique characteristics of normal stem cells and cancer stem cells have been utilized to develop robust stem cell models.…”
Section: Heterogeneity and Unique Characteristics Of Wnt/β-catenin Ac...mentioning
confidence: 99%
“…Interestingly, TPH1 and 5-HTR 7 have been reported to be preferentially expressed in TNBC 114 . In addition, the serotonergic system has also been demonstrated to promote CSC-like activity in BC 116 .…”
Section: Introductionmentioning
confidence: 99%